Somatic mitochondrial DNA mutations in Chinese patients with osteosarcoma. Issue 2 (27th February 2013) - Yu, Man; Wan, Yanfang; Zou, Qinghua
Summary Somatic mutations in mitochondrial DNA (mtDNA) have been long proposed to drive the pathogenesis and progression of human malignancies. Previous investigations have revealed a high frequency of somatic mutations in the D‐loop control region of mtDNA in osteosarcoma. However, little is known with regard to whether or not somatic mutations also occur in the coding regions of mtDNA in osteosarcoma. To test this possibility, in the present study we screened somatic mutations over the full‐length mitochondrial genome of 31 osteosarcoma tumour tissue samples, and corresponding peripheral blood samples from the same cohort of patients. We detected a sum of 11 somatic mutations in the mtDNA coding regions in our series. Nine of them were missense or frameshift mutations that have the potential to hamper mitochondrial respiratory function. In combination with our earlier observations on the D‐loop fragment, 71.0% (22/31) of patients with osteosarcoma carried at least one somatic mtDNA mutation, and a total of 40 somatic mutations were identified. Amongst them, 29 (72.5%) were located in the D‐loop region, two (5%) were in the sequences of the tRNA genes, two (5%) were in the mitochondrial ATP synthase subunit 6 gene and seven (17.5%) occurred in genes encoding components of the mitochondrial respiratory complexes. In addition, somatic mtDNA mutation was not closely associated with the clinicopathological characteristics of osteosarcoma. Together, these findings suggest that somatic mutations are highly prevalent events in both coding and non‐coding regions of mtDNA in osteosarcoma. Some missense and frameshift mutations are putatively harmful to proper mitochondrial activity and might play vital roles in osteosarcoma carcinogenesis.